Humour translation in the age of multimedia - Dore, Margherita (London ; New York : Routledge, 2021)
This volume seeks to investigate how humour translation has developed since the beginning of the 21st century,focusing in particular on new ways of communication. The authors, drawn from a range of countries, cultures and academic traditions, address and debate how today's globalised communication, media and new technologies are influencing and shaping the translation of humour. Examining both how humour translation exploits new means of communicationand how the processes of humour translation may be challenged and enhanced by technologies, the chapters cover theoretical foundations and implications, and methodological practices and challenges. They include a description of current research or practice, and comments on possible future developments. The contributions interconnect around the issue of humour creation and translation in the 21st century, which can truly be labelled as the age of multimedia. Accessible and engaging, this is essential reading for advanced students and researchers in Translation Studies and Humour Studies.
7.2 Communication barriers as a source of humour -- 7.3 Languages far and near -- 7.4 Funny foreigners and evil aliens in stereotypes and parodies -- 7.5 Building a beautiful wall between languages or language profiles? -- 7.6 Closing remarks -- Notes -- References -- 8 A corpus-based approach to the study of subtitling humour -- 8.1 Introduction -- 8.2 Overview of corpus linguistics -- 8.3 A relevance-theoretical framework -- 8.4 Annotation schemes -- 8.5 Corpus design -- 8.6 Data analysis -- 8.7 Conclusion -- Notes -- References
OCLC-licensed vendor bibliographic record.
Keywords: Translating and interpreting; Wit and humor -- Translating; Audio-visual translation; Mass media and language; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting; LANGUAGE ARTS & DISCIPLINES / General